2015
DOI: 10.1002/mawe.201400316
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of copper in LiBr solutions – surface examination

Abstract: Optical microscope (O.M) and scanning electron microscope (SEM) equipped with energy dispersive X‐ray (EDX) were used to follow the changes that occurred on the surfaces of copper after treated electrochemically in concentrated solutions of LiBr (up to 9 M). Results showed the existence of protective film of CuO and Cu(OH)2 which are recorded during the passive film formation in 5 × 10–1 M LiBr at 200 mV. At 1 M LiBr and during the partial passive region (600 mV) a porous film of Cu2O with a small ratio of CuO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…On the other hand, Deslouis et al reported the formation of Cu 2 O as the main constituent of corrosion product layer when copper corroded in aerated medium. El Meleigy et al confirmed the formation of CuO, Cu 2 O, and Cu(OH) 2 by EDX analysis on Cu metal surfaces when immersed in LiBr solution. The results confirmed by this group were in harmony with the result of Pehkonen et al…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…On the other hand, Deslouis et al reported the formation of Cu 2 O as the main constituent of corrosion product layer when copper corroded in aerated medium. El Meleigy et al confirmed the formation of CuO, Cu 2 O, and Cu(OH) 2 by EDX analysis on Cu metal surfaces when immersed in LiBr solution. The results confirmed by this group were in harmony with the result of Pehkonen et al…”
Section: Resultsmentioning
confidence: 97%
“…Since the CuBr is a porous film, the formation of Cu 2 O is possible inside the pores of CuBr according to the following reactions: 2Cu+normalH2OCu2O+2H++2e Cu2O+normalH2O2CuO+2H++e …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are used in the construction of heat exchangers condenser in lithium bromide (LiBr) absorption machines. LiBr heavy brain is widely used as absorbents for almost all type of heating and refrigerating absorption systems (1)(2)(3)(4)(5)(6)(7)(8) .…”
mentioning
confidence: 99%